Perancangan Buku Ilustrasi Panduan Pertolongan Pertama Cedera Olahraga Bola Basket - Ahmad Junaedi; Mahendra Wibawa (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
Basketball injury is a problem of damage at the structure and function of the body because continuous of the stress on physically and mentally when play basketball. The education of injuries and first aid for injuries is important for the future and career sustainability of basketball athletes. Illustration Book Design of First Aid Guide on Basketball Injury to provide information about injuries and how to get first aid of the injuries. Design process of this final project what needs to be done is to identify data from library data sources and field data sources, the next stage is to draw a conclusion from the data that has been obtained. After the conclusion is completed, an answer is drawn to be used as a reference. After a reference is made, the design concept process and design process are carried out, then the digitalitation stage is carried out until the final design. The results obtained from this design is the production of an information tools for first aid of basketball injuries. With the Illustration Book Design of First Aid Guide on Basketball Injury, it’s hoped that it can provide information and education to basketball coaches and athletes so that safety and security in basketball can be maintained.